Biosynthesis of benzyl acetate: Optimization of experimental conditions, kinetic modelling and application of alternative methods for parameters determination. (September 2020) - Gómez, J.L.; Gómez, M.; Murcia, M.D.; Gómez, E.; Hidalgo, A.M.; Montiel, C.; Martínez, R.
Abstract: In this work, the enzymatic synthesis of benzyl acetate by transesterification between the benzyl alcohol and an acyl donor, has been studied. As first objective the selection of the biocatalyst, acyl donor, stirring, solvent and the enzyme amount, was done and, to do this, three immobilized derivatives of commercial lipases, Lipozyme®TLIM, Novozym®40086 and Novozym®435 were tested, being Novozym®435 the immobilized derivative chosen. Vinyl acetate, 300 rpm and n-heptane were selected as acyl donor, stirring and solvent, respectively. As the main objective, the kinetics of the bioprocess was analysed and a bisubstrate Ping-Pong kinetics was proposed. By using two different procedures, the values of the kinetic parameters: Michaelis constants of both substrates and the specific activity of enzyme have been determined. A good level of agreement between the experimental data and the ones calculated with the kinetic model was obtained. Graphical abstract: Unlabelled Image Highlights: Benzyl acetate was synthesized by transesterification with Novozym® 435 lipase. High benzyl acetate conversion was obtained in the best conditions assayed. Enzyme amount is the most significant variable on the reaction rate and yield. A Ping-Pong bisubstrate kinetic model has been proposed for the bioprocess. The parameters of the model, V m, and the sum K MVAc  +  K MBAl, were calculated.